Implementation issues on heritage shophouses facade in Kota Bharu, Kelantan - Y. Mohd Faudzi; N. Md Alwi; N. H. Anuar; S. A. Muhammad; S. N. A. Mohd Nasir; M. R. Mohd Nasir; M. H. K. Mhd Zain (AIP Publishing, 2021)
This study examines the contributing factors behind the continuing trend of non-compliance with heritage facade guidelines by the owners/occupants of heritage shophouses in Kota Bharu, Kelantan. The exterior facade of a heritage building, the crucial element in retaining and safeguarding the features of local and traditional cityscape, includes their associated signage and advertising. A case study on rows of heritage shophouses in Jalan Temenggung became part of a design task to better understand problems encountered in implementing the legislative heritage guidelines entailed for the signages. This exercise, which included site investigation, observation and data collection such as photographic evidence of the selected cases of the shophouses, was carried out by the second-year architecture students from University Malaysia Kelantan (UMK) in September 2019. Analysis of results compares between the existing row of heritage shophouses and a re-creation of shophouse facades by the students in compliance with the heritage guidelines provided by the local authority, Majlis Perbandaran Kota Bharu (MPKB). Discussion curtails on details of mismatched events between existing legislation and guidance against what was observed and applied by current owners. The outcome of this study shares beneficial information to a range of stakeholders which includes the shophouses owners, the local authority, as well as other the heritage conservation practitioners and scholars interested in Kota Bharu, Kelantan.